The analysis of the composition of the wool-washing wastewater (Eurasian Journal of Ecology, 2016)
The analysis of the composition of a wool-washing wastewater primary wool processing factories was carried out. The influence of the composition of the wastewater type and grade to be washed wool wasinvestigated. Were studied the washing effluents from the most common types of wool. Given that the bulk of the pollution are minerals of Kazakhstan wools during washing wool by using surfactants, the main process is to suspend these insoluble suspended solids.
Keywords: wool; mineral; wastewater; composition; pollution